Respuesta :
1) In order to get the systems B, we will replace one equation with the sum/difference of both equations
2) The solutions of both systems are different, hence the systems are not equivalent.
Simultaneous equations are equations that involve two or more unknown variables. These equations can either be linear or quadratic in nature
Given the systems of linear equations
6x−5y=1 ....................1
−2x+2y=−1 ................2
In order to get the systems B as shown. First;
- Add both equations in system A together as shown
equation 1 + equation 2 (System A)
(6x)+(-2x)+ (-5y+2y) = 1 + (-1)
6x - 2x + (-5y+2y) = 1-1
4x + (-3y) = 0
4x - 3y = 0
As you can see, this equation is the result of equation 1 of system B.
Hence in order to get the systems B, we will replace one equation with the sum/difference of both equations
2) Solving both systems to check if they are equivalent.
For system A:
- 6x−5y=1 ....................1 ×2
- −2x+2y=−1 ................2 × 6
Multiply equation 1 by 2 and equation 2 by 6
- 12x−10y=2 ....................1
- −12x+12y=−12 ................2
Add the result
-10y + 12y = 2 -12
2y = -10
y = -10/2
y = -5
Substitute y = 5 into (1)
From 1: 6x−5y=1
6x - 5(-5) = 1
6x + 25 = 1
6x = 1-25
6x = -24
x = -24/6
x = -4
Hence the solution to systems A is (-4, -5)
For system B:
- 4x−3y=1 ....................1 ×2
- −2x+2y=−1 ................2 × 4
Multiply equation 1 by 2 and equation 2 by 4
- 8x−6y=2 ....................1
- −8x+8y=−4 ................2
Add the result
-6y + 8y = 2 -4
2y = -2
y = -2/2
y = -1
Substitute y = -1 into (1)
From 1: 4x−3y=1
4x - 3(-1) = 1
4x + 3 = 1
4x = 1-3
4x = -2
x = -2/4
x = -1/2
Hence the solution to systems B is (-1/2, -1)
Since the solutions of both systems are different, hence the systems are not equaivalent.
Learn more here: https://brainly.com/question/15165519